Correlation of Magnetic Resonance Imaging (Neurography) and Electrodiagnostic Study Findings with Intraoperative Findings in Post Traumatic Brachial Plexus Palsy - Neehar R. Patel; Anupam B. Takwale; K.A Mansukhani; Sunila Jaggi; Mukund R. Thatte (Indian Journal of Plastic Surgery)
Background The majority of brachial plexus injuries (BPIs) are caused by trauma; most commonly due to two-wheeler road accidents. It is important to determine whether the lesion in question is pre-ganglionic or post-ganglionic for purposes of surgical planning and prognosis. Diagnostic testing helps the surgeon to not only decide whether surgical intervention is required, but also in planning the procedure, thereby maximizing the patient's chances of early return to function. The aim of the study was to determine the diagnostic efficacy of electrodiagnostic studies (Edx) and magnetic resonance imaging (MRI) individually, and in unison, in detecting the type and site of BPI by comparison with intraoperative findings (which were used as the reference standard) in patients with posttraumatic BPI. Methods It is an observational cross-sectional prospective randomized study, wherein 48 patients with BPI underwent a detailed clinical and neurological examination of the upper limb, Edx, MRI neurography and were subsequently operated upon. We assessed a total of 240 roots. The diagnosis of all spinal roots was noted on Edx. MRI was performed to look for root avulsion, pseudomeningocoele, and/or rupture injury. The patients were subsequently operated upon. All roots were traced from infraclavicular level right up to the foramen to ensure continuity of root or note rupture/ avulsion. The findings were tabulated. Results MRI accurately diagnosed 138 of the 147 injured roots and MRI sensitivity for the detection of BPI was 93.88%, whereas Edx correctly identified 146 out of 147 injured roots and thus, had sensitivity of 99.32%; however, both lacked specificity (18.28 and 20.43%, respectively). With Edx and MRI in unison, sensitivity was 100% which meant that if a given patient with a BPI is subjected to both tests, not a single abnormal root will go unnoticed. Conclusion Edx and MRI are two highly sensitive investigation modalities whose combined sensitivity is 100% for the detection of a root injury. Therefore, we recommend both tests as they are excellent screening tests.